The altars of Republican Rome and Latium : sacrifice and the materiality of Roman religion - Moser, Claudia (Cambridge : Cambridge University Press, 2019)
This book reorients the study of sacrifice, examining the locus of ritual action - the altars of Republican Rome and Latium.
The organization and boundaries of sacred places -- The economy of ritual: the site-specificity of votive offerings -- The seasonality of ritual: animal sacrifice -- Material memory.
Online resource; title from PDF title page (EBSCO, viewed January 31, 2019).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Almanah ṿeha-aḥim Rom; Rites and ceremonies -- Rome; Sacrifice -- Rome; Altars -- Rome; Rites et cérémonies -- Rome; Sacrifice -- Rome; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Antiquities & Archaeology; Altars; Rites and ceremonies; Sacrifice; Rome (Empire); Altar; Materialität; Opferritus; Römerzeit; Latium